Inflammasomes: Emerging Central Players in Cancer Immunology and Immunotherapy - Karan, Dev (Frontiers in Immunology, 2018)
Inflammation has an established role in cancer development and progression and is a key player in regulating the entry and exit of immune cells in the tumor microenvironment, mounting a significant impact on anti-tumor immunity. Recent studies have shed light on the role of inflammasomes in the regulation of inflammation with a focus on the subsequent effects on the immunobiology of tumors. To generate strong anti-tumor immunity, cross-talk between innate and adaptive immune cells is necessary. Interestingly, inflammasome bridges both arms of the immune system representing a unique opportunity to manipulate the role of inflammation in favor of tumor suppression. In this review, we discuss the impact of inflammasomes on the regulation of the levels of inflammatory cytokines-chemokines and the efficacy of immunotherapy response in cancer treatment.